Contribution to Developing a Topographic Guideline to Organize Sustainable Cadastral Division in Rural Areas - حويجه روز (Latakia University Journal -Engineering Sciences Series, 2024)
This research aims to propose a topographical guideline for organizing sustainable cadastral division in rural areas according to appropriate international engineering standards, which helps in preparing land parcels division for construction in a way that achieves the establishment of residential complexes that are consistent with the rural character and the topographic factor. In terms of the locations of the lots, their areas, and building proportions. An analytical study of horizontal cadastral division works in organized rural areas was conducted by considering new factors such as terrain, topographical inclinations of the land, and building sites and proportions. It was found that there are no engineering division requirements for designing the lots and licensing to build on them in a manner consistent with the contour lines to form a suitable urban environment. This exposes property and infrastructure to the risk of landslides and affects natural resources. A proposal was reached to develop a topographical guideline that governs the procedures for organizing cadastral division in accordance with modern topographical technical rules to ensure sustainable development that protects the unique general character of the countryside from the negative effects of cadastral development, and to be the cornerstone for legislative and technical development to regulate land parcels division in rural areas.